HMGB1-Induced Cross Talk between PTEN and miRs 221/222 in Thyroid Cancer. (27th May 2015) - Mardente, S.; Mari, E.; Massimi, I.; Fico, F.; Faggioni, A.; Pulcinelli, F.; Antonaci, A.; Zicari, A.
Abstract : High mobility group box 1 (HMGB1) is an ubiquitous protein that plays different roles in the nucleus, cytoplasm, and extracellular space. It is an important DAMP molecule that allows communication between damaged or tumor cells and the immune system. Tumor cells exploit HMGB1's ability to activate intracellular pathways that lead to cell growth and migration. Papillary thyroid cancer is a well-differentiated tumor and is often used to study relationships between cells and the inflammatory microenvironment as the latter is characterized by high levels of inflammatory cells and cytokines. Anaplastic thyroid cancer is one of the most lethal human cancers in which many microRNAs and tumor suppressor genes are deregulated. Upregulation of microRNAs 221 and 222 has been shown to induce the malignant phenotype in many human cancers via inhibition of PTEN expression. In this study we suggest that extracellular HMGB1 interaction with RAGE enhances expression of oncogenic cluster miR221/222 that in turn inhibits tumor suppressor gene PTEN in two cell lines derived from human thyroid anaplastic and papillary cancers. The newly identified pathway HMGB1/RAGE/miR221/222 may represent an effective way of tumor escape from immune surveillance that could be used to develop new therapeutic strategies against anaplastic tumors.